THE ROLE OF ENDOTHELIAL PROGENITOR CELLS ON VASCULAR REGENERATION PROCESS - Katrin **; Desak Made Wihandani (E-Jurnal Medika Udayana, 2013)
Background: Endothelial progenitor cells (EPCs) possesses an enormous potential in regenerating   blood   vessels   and   maintain   its   integrity   and   elasticity   through angiogenesis, vasculogenesis, and neovascularization, mainly during reperfusion after ischemia. However, to date, there has been no universal consensus regarding the precise definition of EPCs due to highly variable cell-based research in this growing field. Aim of study: This review aims to elucidate the various approach to classify EPC subtypes. Moreover, we also elaborate the EPCs signaling mechanism, comprising the cytokines  and  growth  factors  involved  in  EPCs  receptor  expression,  migration, adhesion, invasion, and differentiation process into mature endothelial cells. Method: This review summarizes the contemporary EPCs subtype classification as well as their role in neovascularization and endothelial regeneration through extensive literature discoveries and synthesis, comprising mainly research articles. Results: EPCs classification can be derived from several approaches, including in vitro adhesion assay, antigen surface markers, cellular morphology, specific characteristics (non-ingestion), and ability to form tube in vitro and blood vessels in vivo. EPCs mainly are derived bone marrow and mobilized during ischemia and inflammation. A number of cytokines and growth factors have been known to induce. Conclusion: EPCs play a crucial role in neovascularization and angiogenesis process in times  of  ischemia  or  inflammation.  However,  to  date,  there  has  been  no  precise definition regarding EPCs identity. Its identity must be ideally confirmed and unified in a single international consensus before stepping further into a more sophisticated therapeutic strategies by utilizing these cell-based technology.